Square planar Cu(i) stabilized by a pyridinediimine ligand. Issue 22 (23rd February 2016) - Cheung, Pui Man; Berger, Robert F.; Zakharov, Lev N.; Gilbertson, John D.
Abstract : A set of distorted square planar Cu(i ) complexes were synthesized and characterized utilizing the sterically encumbering pyridinediimine ligand, iPr PDI (where iPr PDI = 2, 6-(2, 6- i Pr2 C6 H3 NCMe)2 C5 H3 N). Abstract : A set of distorted square planar Cu(i ) complexes were synthesized and characterized utilizing the sterically encumbering pyridinediimine ligand, iPr PDI (where iPr PDI = 2, 6-(2, 6- i Pr2 C6 H3 NCMe)2 C5 H3 N). The oxidation state of the Cu center(s) were elucidated to be Cu(i ) with a neutral PDI ligand system based on structural, spectroscopic, and computational data.